2001
DOI: 10.1016/s0006-3495(01)76183-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tryptophan Fluorescence Shifts in Proteins

Abstract: Tryptophan fluorescence wavelength is widely used as a tool to monitor changes in proteins and to make inferences regarding local structure and dynamics. We have predicted the fluorescence wavelengths of 19 tryptophans in 16 proteins, starting with crystal structures and using a hybrid quantum mechanical-classical molecular dynamics method with the assumption that only electrostatic interactions of the tryptophan ring electron density with the surrounding protein and solvent affect the transition energy. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
1,163
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,283 publications
(1,229 citation statements)
references
References 83 publications
61
1,163
1
4
Order By: Relevance
“…23 Their work extended previous findings, 24 where fluorescent shifts were reasonably predicted using only electrostatic interactions between the chromophore and the protein. In both cases the chromophore was modeled by 3-methylindole.…”
Section: Introductionsupporting
confidence: 77%
“…23 Their work extended previous findings, 24 where fluorescent shifts were reasonably predicted using only electrostatic interactions between the chromophore and the protein. In both cases the chromophore was modeled by 3-methylindole.…”
Section: Introductionsupporting
confidence: 77%
“…Recent work has shown that Trp exposure to water molecules had less influence on the maximum emission wavelength than the residues lying close to the Trp [34,35]. The studies show that the presence of positive charges (Lys, Arg, N-terminal) create a red shift when on the benzene ring end and a blue shift when on the pyrrole ring end, and the reverse for the negative charges (Glu, Asp and C-terminal) [35]. Thus, if the Trps had a particular environment in the native gC1q, the blue shift could arise from its loss upon the acidic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a higher ratio is indicative of the tryptophan residues becoming exposed to a more polar environment. 34,35 Based on our experience, fulllength mAbs exhibit F 350 /F 330 values from »0.6 to »1. For mAb1, the ratio ranges from 0.75 for mAb1*_WT to 0.69 for mAb1_Hv2_Lv3, and thus falls within a narrow range compared to the variability between various full-length mAbs.…”
Section: Biophysical Characterizationmentioning
confidence: 99%